Revisional surgery after one anastomosis/mini gastric bypass: A narrative review - Mohammad Kermansaravi (Journal of Research in Medical Sciences, 2020)
One anastomosis gastric bypass (OAGB)/mini gastric bypass is now considered to be a safe and efficient method for morbidly obese patients but has complications and adverse events such as other surgical procedures. The present paper outlines the need for and the nature of revisional surgery in the long-term following OAGB in accordance with the preferred reporting items for systematic reviews and meta-analysis guidelines. A literature search was carried out in PubMed. All articles on OAGB for which the authors described a patient needing revisional surgery in the long term after OAGB were examined.